Vận dụng cách tiếp cận và lý thuyết trong nghiên cứu chính sách dân tộc về văn hóa - xã hội trên địa bàn tỉnh Lâm Đồng - Đào, Thị Hiếu (Viện Nghiên cứu và ứng dụng công nghệ giáo dục ATEC, Hiệp hội các trường đại học, cao đẳng Việt Nam, 2025)
Ethnic policies on culture and society play an important role in the development process of ethnic minority areas. The approach and theory will be the foundation for implementing research on the economic, cultural and social fields in practice. This article deals with the basic content of the interdisciplinary approach, the community development approach based on internal resources; and theories such as development theory, social system theory. In addition, the article applies this approach and theory to explain aspects in the research on ethnic policies on culture and society in ethnic minority areas.